Active carbon for high-rate supercapacitor and preparation method thereof

CN121215442BActive Publication Date: 2026-10-30FUJIAN XINSEN CARBON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511369094.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2026-10-30
Estimated Expiration
2045-09-24

AI Technical Summary

Technical Problem

[0006]为解决上述活性炭倍率性能差的技术问题,本发明首先用植酸、羟基苯甲醛衍生物反应制得醛基改性植酸,然后用醛基改性植酸对预氧化处理后的煤沥青进行改性得改性沥青母粒,最后改性沥青母粒按一定比例与煤沥青、活化剂混合,再进行炭化、活化制得具有优异导电性和倍率性能的超级电容器用活性炭

Benefits of technology

[0029]本发明首先用植酸、羟基苯甲醛衍生物反应制得醛基改性植酸,然后用醛基改性植酸对预氧化处理后的煤沥青进行改性得改性沥青母粒,最后改性沥青母粒按一定比例与煤沥青、活化剂混合,再进行炭化、活化制得高倍率超级电容器用活性炭。改性沥青母粒中醛基改性植酸通过反应化学键接在煤沥青中的化合物分子上,形成高浓度、均匀分散的母粒,将改性沥青母粒与煤沥青按一定比例混合,相似相容原理使二者很容易混合均匀,进而键接的醛基改性植酸均匀分布在混合物中;醛基改性植酸兼具磷源和活化剂的作用,一方面已经均匀分布的醛基改性植酸会发挥活化剂的作用,弥补机械共混活化剂不均导致的缺陷,优化孔结构,提高导电性,另一方面,磷元素通过P-C键,掺杂到碳骨架中,降低电阻,最终实现活性炭导电性、倍率性能的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005611102280000061
    Figure BDA0005611102280000061
Patent Text Reader

Abstract

The present application belongs to the technical field of activated carbon for supercapacitor, and particularly relates to an activated carbon for high-rate supercapacitor and a preparation method thereof, comprising the following steps: 1) performing esterification reaction on phytic acid and hydroxybenzaldehyde derivative under the action of a carbodiimide condensing agent to obtain aldehyde-modified phytic acid; 2) performing pre-oxidation treatment on coal tar, and then dissolving the coal tar, the aldehyde-modified phytic acid and a catalyst in an organic solvent under an inert atmosphere, controlling the temperature to react, performing vacuum distillation, and crushing to obtain modified pitch master granules; and 3) mixing the coal tar and the modified pitch master granules, carbonizing the mixture, activating and forming pores on the obtained carbonized product to obtain the activated carbon for high-rate supercapacitor. The aldehyde-modified phytic acid in the modified pitch master granules is chemically bonded to the compound molecules in the coal tar through a reaction, forming high-concentration and uniformly dispersed master granules. When the modified pitch master granules are mixed with the coal tar, the aldehyde-modified phytic acid has the functions of a phosphorus source and an activator, reduces the resistance, and finally improves the conductivity and the rate performance of the activated carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of activated carbon technology, specifically relating to activated carbon for high-rate supercapacitors and its preparation method. Background Technology

[0002] Supercapacitors are a new type of energy storage device developed in recent years, with performance falling between that of traditional capacitors and batteries. They can provide energy density hundreds of times higher than traditional capacitors and power density tens of times higher than batteries, while also offering extremely fast charging and discharging speeds and long cycle life. Therefore, they have broad market prospects and enormous commercial value in many fields such as electric vehicles, aerospace, military, and the electronics industry.

[0003] Supercapacitors mainly consist of electrodes, a separator, an electrolyte, and a current collector, with the electrodes being the core component, determining the fundamental electrochemical performance of the supercapacitor. Currently reported electrode materials include carbon materials, metal oxides, and conductive polymers. Among these, carbon materials have attracted significant attention due to their large specific surface area and low cost. Carbon materials primarily include activated carbon, activated carbon fibers, carbon aerogels, carbon nanotubes, and mesoporous carbon materials. Activated carbon has a long history of industrial production and application, and its raw materials are abundant and inexpensive, making it the earliest material used in supercapacitor electrodes. Many types of activated carbon are produced, mainly categorized as wood-based and mineral-based. Production of activated carbon is limited due to the scarcity of wood resources; mineral-based activated carbons, such as coal tar pitch and petroleum pitch, have stable resources and have received widespread attention. For example, patent CN100335407C discloses activated carbon, its manufacturing method, and polarizable electrodes, which involve adding alkaline earth metal compounds to pitch materials and then subjecting them to heat treatment and activation. Patent CN111547721B discloses a method for preparing mesoporous activated carbon for supercapacitors. The method of the present invention uses coal tar pitch and gel as raw materials and then performs modification treatment, pretreatment, homogenization treatment, activation and post-treatment steps to obtain activated carbon for supercapacitors.

[0004] The above is a study on the preparation of activated carbon using coal tar pitch rich in aromatic structures and high carbon content. The activated carbon obtained has the advantages of well-developed pore structure, high specific surface area and excellent energy storage performance. However, the viscosity of coal tar pitch itself is relatively high, and it is easy to mix unevenly when mixed with activators and pore-forming agents, resulting in local over-etching, local blanks, poor continuity of conductive network and ion channels, and affecting the conductivity and rate performance of activated carbon.

[0005] Therefore, developing an activated carbon electrode material with optimized pore structure, high specific surface area, and good conductivity is of great significance for improving the rate performance of supercapacitors to achieve fast charging and fast high-current discharge, and for the widespread application of supercapacitors, especially in the field of electric vehicles. Summary of the Invention

[0006] To address the aforementioned technical problem of poor rate performance of activated carbon, this invention first prepares aldehyde-modified phytic acid by reacting phytic acid with hydroxybenzaldehyde derivatives. Then, the aldehyde-modified phytic acid is used to modify pre-oxidized coal tar pitch to obtain modified pitch masterbatch. Finally, the modified pitch masterbatch is mixed with coal tar pitch and an activator in a certain proportion, and then carbonized and activated to obtain activated carbon for supercapacitors with excellent conductivity and rate performance.

[0007] A method for preparing activated carbon for high-rate supercapacitors includes the following steps:

[0008] 1) Phytic acid and hydroxybenzaldehyde derivatives undergo a reverse esterification reaction under the action of a carbodiimide condensing agent to obtain aldehyde-modified phytic acid;

[0009] 2) Coal tar pitch is first pre-oxidized, and then coal tar pitch, aldehyde-modified phytic acid, and catalyst are dissolved in an organic solvent under an inert atmosphere, reacted under controlled temperature, distilled under reduced pressure, and crushed to obtain modified pitch masterbatch.

[0010] 3) After mixing coal tar pitch and modified pitch masterbatch, carbonize them, and then activate the carbonized product to form pores to obtain activated carbon for high-rate supercapacitors.

[0011] In step 1), the molar ratio of phytic acid, hydroxybenzaldehyde derivative, and carbodiimide condensing agent is 1:1-3.5:2-3.5.

[0012] In step 1), the molar ratio of phytic acid, hydroxybenzaldehyde derivative, and carbodiimide condensing agent is 1:1.5-2.5:2-3.5.

[0013] In step 1), the hydroxybenzaldehyde derivative is selected from one or more combinations of 3-methoxy-4-hydroxybenzaldehyde, 3-ethoxy-4-hydroxybenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, and salicylaldehyde.

[0014] In step 1), the carbodiimide condensing agent is selected from one or a combination of two of N,N'-dicyclohexylcarbodiimide, diisopropyldiimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.

[0015] In step 1), the esterification reaction is specifically as follows: under an inert atmosphere, phytic acid, hydroxybenzaldehyde derivatives, and carbodiimide condensing agents are dissolved in an organic solvent, and the reaction is carried out at a controlled temperature to obtain aldehyde-modified phytic acid.

[0016] The temperature-controlled reaction is 90-150℃, and the reaction time is 2-10 hours. The organic solvent is selected from one or more combinations of DMF and DMSO.

[0017] The temperature-controlled reaction technique further includes post-processing operations: adding ice water to the system obtained after the temperature-controlled reaction, filtering, extraction, washing with dilute hydrochloric acid, separating and retaining the organic phase, washing with saturated brine, drying, filtering, and distillation. The solvent used for extraction is selected from one or a combination of two of ethyl acetate and dichloromethane. The dilute hydrochloric acid washing is performed 2-3 times with a 1-2 mol / L hydrochloric acid solution, with each wash using 1 / 4-1 / 3 of the volume of the dilute hydrochloric acid solution as the organic phase. The saturated brine washing is performed 1-2 times. The drying is performed by adding a desiccant, which is selected from one or a combination of two or more of magnesium sulfate, sodium sulfate, calcium chloride, and magnesium chloride.

[0018] In step 2), the mass ratio of coal tar pitch, aldehyde-modified phytic acid, catalyst, and organic solvent is 0.55-0.7:0.3-0.45:0.01-0.03:4-8.

[0019] In step 2), the coal tar pitch has an average particle size of 50-100 mesh and a softening point of 70-150℃, preferably 70-90℃. The catalyst is p-toluenesulfonic acid.

[0020] In step 2), the pre-oxidation treatment is a heat treatment at 200-300℃ for 1-2 hours in an oxygen atmosphere. After pre-oxidation, coal tar pitch will produce groups that can react with the aldehyde groups on aldehyde-modified phytic acid, such as phenolic hydroxyl groups and carboxyl groups.

[0021] In step 2), the organic solvent is selected from one or more combinations of benzene, toluene, xylene, ethyl acetate, and dichloromethane, preferably a mixed solvent with a toluene-ethyl acetate volume ratio of 5.5-10:1. The temperature-controlled reaction is carried out at 50-70℃ for 4-6 hours. The vacuum distillation is carried out at a vacuum of 0.06-0.08 MPa and a temperature of 30-60℃ for 1-3 hours. The crushing is carried out to an average particle size of 100-200 mesh.

[0022] Step 1) is the reaction of hydroxybenzaldehyde derivative with phytic acid. Phytic acid has 6 phosphate groups. Under the action of a condensing agent, the phosphate groups and the hydroxyl groups on the hydroxybenzaldehyde derivative undergo an esterification reaction to generate aldehyde-modified phytic acid. Within a certain range, as the relative amount of hydroxybenzaldehyde derivative increases, the aldehyde-modified phytic acid has more aldehyde groups. Step 2) is the step of grafting the modified aldehyde group of phytic acid onto the pre-oxidized coal tar pitch by reacting the modified aldehyde group with the phenolic hydroxyl group of the pre-oxidized coal tar pitch to obtain modified pitch masterbatch.

[0023] Because the reaction between aldehyde groups and phenolic hydroxyl groups grafts aldehyde-modified phytic acid onto pre-oxidized coal tar pitch, the aldehyde-modified phytic acid also acts as a bridge, causing cross-linking reactions between molecules containing phenolic hydroxyl groups in the coal tar pitch. Therefore, the relative amount of hydroxybenzaldehyde derivatives to phytic acid needs to be controlled within a certain range. Too little phytic acid cannot solve the problems of localized over-etching and blank areas on activated carbon, while too much phytic acid will lead to excessive cross-linking of the modified pitch. During activation, the activator (such as KOH) will have difficulty penetrating into the carbon skeleton, forming only shallow pores on the surface. This results in a small specific surface area, a low mesopore volume ratio, and still poor electrochemical performance of the activated carbon. Therefore, the molar ratio of phytic acid to hydroxybenzaldehyde derivatives must be strictly controlled.

[0024] In step 3), the mass ratio of coal tar pitch to modified asphalt masterbatch is 1-3:1.

[0025] In step 3), the average particle size of the coal tar pitch is 100-200 mesh and the softening point is 70-150℃, preferably 90-150℃.

[0026] In step 3), the mass ratio of the carbonized product to the activator is 1:1.5-2.5. The activator is selected from one or a combination of two of potassium hydroxide and sodium hydroxide.

[0027] In step 3), the carbonization is carried out under an inert atmosphere, with the temperature increased at a rate of 1-3℃ / min to 400-550℃, and treated for 1-2 hours. The activation is carried out under an inert atmosphere, with the temperature increased at a rate of 3-5℃ / min to 700-900℃, and treated for 1-3 hours. After activation, the following operations are also included: cooling, acid washing, water washing, drying, and grinding. The cooling is to cool to 20-40℃. The acid washing is to wash 1-3 times with hydrochloric acid with a concentration of 1-2 mol / L. The water washing is to wash with water until the pH is 6.5-7. The drying is to dry at 100-120℃ for 10-18 hours. The grinding is to grind to an average particle size of 5-10 μm.

[0028] Compared with the prior art, the beneficial effects of the present invention are:

[0029] This invention first prepares aldehyde-modified phytic acid by reacting phytic acid with hydroxybenzaldehyde derivatives. Then, it modifies pre-oxidized coal tar pitch to obtain modified pitch masterbatch. Finally, the modified pitch masterbatch is mixed with coal tar pitch and an activator in a certain proportion, followed by carbonization and activation to obtain activated carbon for high-rate supercapacitors. In the modified pitch masterbatch, the aldehyde-modified phytic acid is chemically bonded to compounds in the coal tar pitch, forming a high-concentration, uniformly dispersed masterbatch. Mixing the modified pitch masterbatch and coal tar pitch in a certain proportion allows for easy and uniform mixing based on the principle of similar compatibility, resulting in a uniform distribution of the bonded aldehyde-modified phytic acid in the mixture. The aldehyde-modified phytic acid acts as both a phosphorus source and an activator. On one hand, the uniformly distributed aldehyde-modified phytic acid acts as an activator, compensating for defects caused by uneven mechanical blending of activators, optimizing pore structure, and improving conductivity. On the other hand, phosphorus is incorporated into the carbon skeleton through PC bonds, reducing resistance and ultimately improving the conductivity and rate performance of the activated carbon. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, all "parts" mentioned in the embodiments of the present invention are parts by weight. All reagents used are commercially available in the art.

[0031] Coal tar pitch 1 has an average particle size of 50 mesh and a softening point of 89℃, and comes from Handan Ruibo Coal Chemical Co., Ltd.

[0032] Coal tar pitch 2 has an average particle size of 100 mesh and a softening point of 117℃, and comes from Handan Ruibo Coal Chemical Co., Ltd.

[0033] Example 1

[0034] 1) Under a nitrogen atmosphere, 0.1 mol of phytic acid, 0.25 mol of p-hydroxybenzaldehyde, and 0.35 mol of N,N'-dicyclohexylcarbodiimide were dissolved in 250 parts by mass of DMSO. The mixture was reacted at 130℃ for 4 h. An equal volume of ice water was added to the mixture. The insoluble matter was removed by filtration. The mixture was extracted with ethyl acetate and washed with 1 / 3 the volume of dilute hydrochloric acid (2 mol / L) of the extracted organic phase. The washing was repeated twice. The organic phases were separated and combined. The mixture was washed with 1 / 3 the volume of saturated brine of the combined organic phase. The washing was repeated twice. Magnesium sulfate was added for drying. The desiccant was removed by filtration. Finally, the solvent was removed by distillation to obtain aldehyde-modified phytic acid.

[0035] 2) Coal tar pitch 1 was first heat-treated in oxygen at 200℃ for 2 hours. Then, under a nitrogen atmosphere, 55 parts by mass of coal tar pitch 1, 45 parts by mass of aldehyde-modified phytic acid, and 3 parts by mass of p-toluenesulfonic acid were dissolved in 400 parts by mass of a mixed solvent composed of toluene and ethyl acetate in a volume ratio of 10:1. The mixture was reacted at 70℃ for 4 hours. The mixture was then distilled at 45℃ under a vacuum of 0.06 MPa for 1 hour and crushed to an average particle size of 100 mesh to obtain modified pitch masterbatch.

[0036] 3) Mix 100 parts by weight of coal tar pitch and 100 parts by weight of modified asphalt masterbatch in a mixer. Under a nitrogen atmosphere, heat the mixture at a rate of 3℃ / min to 550℃ and carbonize it for 1 hour. Mix the resulting carbonized product with potassium hydroxide at a mass ratio of 1:2.5. Under a nitrogen atmosphere, heat the mixture at a rate of 5℃ / min to 900℃ and activate it for 2 hours. Allow it to cool naturally to room temperature (25℃), wash it twice with 2 mol / L hydrochloric acid, wash it with water until the pH reaches 7, dry it at 120℃ for 12 hours, and grind it to an average particle size of 7.55 μm to obtain activated carbon for high-rate supercapacitors.

[0037] Example 2

[0038] The rest is the same as in Example 1, except that in step 1), equimolar amounts of 3-methoxy-4-hydroxybenzaldehyde are used instead of p-hydroxybenzaldehyde.

[0039] Example 3

[0040] The rest is the same as in Example 1, except that in step 1), the amount of p-hydroxybenzaldehyde used is 0.15 moles.

[0041] Example 4

[0042] The rest is the same as in Example 1, except that in step 1), the amount of p-hydroxybenzaldehyde used is 0.1 moles.

[0043] Example 5

[0044] The rest is the same as in Example 1, except that in step 1), the amount of p-hydroxybenzaldehyde used is 0.35 moles.

[0045] Example 6

[0046] The rest is the same as in Example 1, except that in step 2), the amount of coal tar pitch 1 is 70 parts by mass and the amount of aldehyde-modified phytic acid is 30 parts by mass.

[0047] Example 7

[0048] The rest is the same as in Example 1, except that in step 3), the amount of coal tar pitch 2 is 300 parts by mass and the amount of modified asphalt masterbatch is 100 parts by mass.

[0049] Example 8

[0050] 1) Under a nitrogen atmosphere, 0.1 mol of phytic acid, 0.25 mol of p-hydroxybenzaldehyde, and 0.35 mol of N,N'-dicyclohexylcarbodiimide were dissolved in 250 parts by mass of DMSO. The mixture was reacted at 150℃ for 2 h. An equal volume of ice water was added to the mixture. The insoluble matter was removed by filtration. The mixture was extracted with ethyl acetate and washed with 1 / 3 the volume of dilute hydrochloric acid (2 mol / L) twice. The organic phases were separated and combined. The organic phases were washed with 1 / 3 the volume of saturated brine twice. Magnesium sulfate was added for drying. The desiccant was removed by filtration and the solvent was removed by distillation to obtain aldehyde-modified phytic acid.

[0051] 2) Coal tar pitch 1 was first heat-treated in oxygen at 300℃ for 1 hour. Then, under a nitrogen atmosphere, 55 parts by mass of coal tar pitch 1, 45 parts by mass of aldehyde-modified phytic acid, and 3 parts by mass of p-toluenesulfonic acid were dissolved in 400 parts by mass of a mixed solvent composed of toluene and ethyl acetate in a volume ratio of 10:1. The mixture was reacted at 70℃ for 4 hours. The mixture was then distilled at 45℃ under a vacuum of 0.06 MPa for 1 hour and crushed to an average particle size of 100 mesh to obtain modified pitch masterbatch.

[0052] 3) Mix 100 parts by weight of coal tar pitch and 100 parts by weight of modified asphalt masterbatch in a mixer. Under a nitrogen atmosphere, heat the mixture at a rate of 3℃ / min to 500℃ and carbonize for 1.5h. Mix the resulting carbonized product with potassium hydroxide at a mass ratio of 1:1.5. Under a nitrogen atmosphere, heat the mixture at a rate of 5℃ / min to 900℃ and activate it for 2h. Allow it to cool naturally to room temperature (25℃), wash it twice with 2mol / L hydrochloric acid, wash it with water until the pH reaches 7, dry it at 120℃ for 12h, and grind it to an average particle size of 7.81μm to obtain activated carbon for high-rate supercapacitors.

[0053] Comparative Example 1

[0054] 100 parts by mass of coal tar pitch 2 were heated to 550℃ at a rate of 3℃ / min under a nitrogen atmosphere and carbonized for 1 hour. The resulting carbonized product was mixed with potassium hydroxide at a mass ratio of 1:2.5 and heated to 900℃ at a rate of 5℃ / min under a nitrogen atmosphere for 2 hours to activate it. It was then naturally cooled to room temperature (25℃), washed twice with 2 mol / L hydrochloric acid, washed with water until the pH reached 7, dried at 120℃ for 12 hours, and ground to an average particle size of 100 mesh to obtain activated carbon for high-rate supercapacitors.

[0055] Application examples

[0056] Electrode sheet preparation: According to the mass percentage ratio of activated carbon, binder PVDF and conductive agent acetylene black 80:12:8, first dissolve the binder in N-methylpyrrolidone to prepare a 0.02 g / ml solution, then add activated carbon and conductive agent to the binder solution and stir evenly to form a paste. Coat the paste onto the nickel foam current collector, then dry it in a vacuum drying oven at 100℃ for 12 h, press it into tablets at 20 MPa on a tablet press, and cut it into electrode sheets to obtain the electrode sheet.

[0057] Assemble the supercapacitor: Place the electrode sheet / porous polypropylene separator / electrode sheet into the button cell casing in sequence to form a sandwich structure with two electrodes, then add 6 mol / L KOH electrolyte and encapsulate it into a CR2032 type button supercapacitor.

[0058] The activated carbon prepared in the above examples and comparative examples was subjected to the following performance tests:

[0059] 1. Specific surface area and pore structure: Measured using a NOVA 1000e pore structure and specific surface area analyzer. Samples were degassed at 350℃ for 2 hours, using liquid nitrogen as the adsorption medium, at 77K and a relative pressure (P / P0) of 10. -6 N2 adsorption was measured within the range of -1, and the specific surface area and pore size distribution were obtained by the BET equation and the BJH equation, respectively.

[0060] 2. Constant current charge-discharge method: The constant current charge-discharge test of the coin-type supercapacitor was carried out using the battery testing system (CT3001A) of Wuhan Landian Electronics Co., Ltd., and the specific capacitance at current densities of 1A / g, 5A / g and 20A / g was recorded. The retention rate of the specific capacitance at current densities of 5A / g and 20A / g relative to the specific capacitance at current density of 1A / g was calculated respectively.

[0061] 3. Cyclic performance: Long-term cycle performance was tested using the battery testing system (CT3001A) of Wuhan Landian Electronics Co., Ltd. At a current density of 5A / g, the supercapacitor underwent 10,000 constant current charge-discharge cycles, and the specific capacitance retention rate was calculated.

[0062] Table 1 Performance Test Results

[0063]

[0064] As shown in Table 1, the activated carbon prepared by this invention has a high specific capacity, which can significantly improve the rate performance and cycle life of supercapacitors under high current and high current density. It is suitable for high-power, short-time discharge applications, such as the instantaneous acceleration of electric vehicles and the fast charging of buses. At a current density of 1 A / g, the specific capacity of activated carbon reaches 298-338 F / g. At a current density of 5 A / g, the cycle life of supercapacitors reaches 83.2-100% after 10,000 constant current charge and discharge cycles.

[0065] The electrochemical performance test results show that, within a certain range, the more aldehyde-modified phytic acid or modified asphalt masterbatch is used, the more suitable the pore structure of the prepared activated carbon is for ion migration under low current density. Appropriately reducing the amount of aldehyde-modified phytic acid or modified asphalt masterbatch will result in activated carbon that is more suitable for high current and high frequency impact, which is beneficial to improving the capacity retention rate under high current density and the cycle life under a current density of 5A / g.

Claims

1. A method for preparing activated carbon for high-rate supercapacitors, characterized in that, Includes the following steps: 1) Phytic acid and hydroxybenzaldehyde derivatives are esterified under the action of carbodiimide condensing agents to obtain aldehyde-modified phytic acid; 2) Coal tar pitch is first pre-oxidized, and then coal tar pitch, aldehyde-modified phytic acid, and catalyst are dissolved in an organic solvent under an inert atmosphere, reacted under controlled temperature, distilled under reduced pressure, and crushed to obtain modified pitch masterbatch. 3) After mixing coal tar pitch and modified asphalt masterbatch, carbonize them, and activate the carbonized product to form pores to obtain activated carbon for high-rate supercapacitors; In step 1), the molar ratio of phytic acid, hydroxybenzaldehyde derivative and carbodiimide condensing agent is 1:1-3.5:2-3.

5.

2. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 1), the molar ratio of phytic acid, hydroxybenzaldehyde derivative, and carbodiimide condensing agent is 1:1.5-2.5:2-3.

5.

3. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 1), the hydroxybenzaldehyde derivative is selected from one or more of 3-methoxy-4-hydroxybenzaldehyde, 3-ethoxy-4-hydroxybenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, and salicylaldehyde; and / or the carbodiimide condensing agent is selected from one or more of N,N'-dicyclohexylcarbodiimide, diisopropyldiimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.

4. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 1), the esterification reaction is specifically as follows: under an inert atmosphere, phytic acid, hydroxybenzaldehyde derivatives, and carbodiimide condensing agents are dissolved in an organic solvent, and the reaction is carried out at a controlled temperature to obtain aldehyde-modified phytic acid.

5. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 2), the mass ratio of coal tar pitch, aldehyde-modified phytic acid, catalyst, and organic solvent is 0.55-0.7:0.3-0.45:0.01-0.03:4-8.

6. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 2), the average particle size of the coal tar pitch is 50-100 mesh and the softening point is 70-150℃; the catalyst is p-toluenesulfonic acid.

7. The method for preparing activated carbon for high-rate supercapacitors according to claim 6, characterized in that, In step 2), the softening point of the coal tar pitch is 70-90℃.

8. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 2), the pre-oxidation treatment is heat treatment at 200-300℃ for 1-2 hours in an oxygen atmosphere; the crushing is crushing to an average particle size of 100-200 mesh.

9. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 3), the mass ratio of coal tar pitch to modified asphalt masterbatch is 1-3:1; the average particle size of the coal tar pitch is 100-200 mesh and the softening point is 70-150℃.

10. The method for preparing activated carbon for high-rate supercapacitors according to claim 9, characterized in that, In step 3), the softening point of the coal tar pitch is 90-150℃.

11. The method for preparing activated carbon for high-rate supercapacitors according to claim 1, characterized in that, In step 3), the mass ratio of the carbonized product to the activator is 1:1.5-2.5; the activator is selected from one or a combination of potassium hydroxide and sodium hydroxide.

12. An activated carbon for high-rate supercapacitors, characterized in that, It is prepared by the method described in any one of claims 1-11.

Citation Information

Patent Citations

  • Active carbon, production method thereof and polarizable electrode

    CN100335407C

  • A method for preparing mesoporous activated carbon for supercapacitors

    CN111547721B

  • Nitrogen and phosphorus co-doped carbon nanosheet and preparation method thereof, alkali metal ion battery electrode, alkali metal ion battery and electric device

    CN109970043A

  • Preparation method of hard carbon negative electrode material

    CN115504452A